2020
DOI: 10.1111/vsu.13382
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective assessment of perioperative antimicrobial use for elective arthroscopy in horses

Abstract: Objective To describe perioperative antimicrobial use in horses undergoing elective arthroscopy. Study design. Retrospective study. Sample population. Horses that underwent elective arthroscopy at one institution between July 2016 and May 2018, excluding those with a suspected infectious orthopedic disease or with a comorbidity that may have impacted prophylactic antimicrobial use decisions. Methods Medical records were reviewed to evaluate preoperative, intraoperative, and postoperative antimicrobial drug sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 24 publications
(50 reference statements)
2
23
0
Order By: Relevance
“…In audit 1, 37.5% of the arthroscopies met the <60-min threshold for tAB-INC. However, this percentage increases to 72% if only single joint arthroscopies are considered, which compares favorably to the study by Muntwyler et al where primarily one-joint arthroscopies (66.3% of cases) were included (10). This also highlights the critical contribution of tPREP to tAB-INC as the number of operated joints increases.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…In audit 1, 37.5% of the arthroscopies met the <60-min threshold for tAB-INC. However, this percentage increases to 72% if only single joint arthroscopies are considered, which compares favorably to the study by Muntwyler et al where primarily one-joint arthroscopies (66.3% of cases) were included (10). This also highlights the critical contribution of tPREP to tAB-INC as the number of operated joints increases.…”
Section: Discussionsupporting
confidence: 76%
“…However, our results for tAB-INC are approximately half of that previously reported for arthroscopies (142 min) by a different institution, with different hospital policies (9). A retrospective study conducted by the same institution reported an improvement in their rate of arthroscopies achieving a tAB-INC < 60 min; improving from 6.3 to 40.2% (10). It is possible that the hospital policy regarding antimicrobial prophylaxis was modified after the first study, but the factors that contributed to this improvement were not described in the second study.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…This retrospective study by Noah Muntwyler and colleagues in Canada aimed to describe perioperative antimicrobial use in horses undergoing elective arthroscopy.…”
Section: Perioperative Antimicrobials For Arthroscopymentioning
confidence: 99%